Pengembangan Metode Demonstrasi Menggunakan Lembar kerja Siswa (LKS) Simulasi Online pada Materi Fluida - Agus Umaeza; Widodo Widodo (Jurnal Penelitian Pembelajaran Fisika, 2017)
This study aims to describe the process of developing a demonstration method using Student Activity Sheet (LKS) with an online similation approach on fluid material, and producing Student Activity Sheets that meet valid, practical, and effective criteria. This research is a development research using the model of device development according to Thiagarajan, without spreading stage. A limited trial was conducted in class XI IPA 1 MAN Majenanag odd semester of academic year 2017/2018 with 38 students. In this study, the data obtained from the validation by the validator, the results of student work on the test results of learning, and filling the questionnaire response students. Based on the analysis results obtained that the LKS development process refers to the model according Thiagarajan which is limited to the development stage. The result of the development is LKS with an online simulation approach on fluid material that meets the valid, practical, and effective criteria